The effect of stress on the hematological indicators of rats Rattus Norvegicus F. Domesticus in the conditions of the biological experiment - L.O. Shevchyk; N.Ya. Kravets; I.M. Grod (Medičnì Perspektivi)
The purpose of the work was the need to study the change in weight and hematological indicators of the rats as a reaction-response to being in difficult and unfavorable experimental conditions. The biological experiment was conducted in compliance with the normative conditions of keeping the rats, in accordance with ethical standards and recommendations for humanization of work with laboratory animals. In order to accomplish these tasks, rats were divided into two groups: control rats were housed in a spacious cage with comfortable living conditions and experimental animals were housed in a small cage with limited ability to move freely. For the purity of the experiment, the feed ration of animals of two groups was the same. Weight and hematological indicators were determined by conventional methods in physiology. It has been found that improper housing conditions, causing a stressful situation adversely affect the eating activity of the test animals, which explains the weak correlation of the dynamics of the weight of the animals in the control and experimental groups. The analysis of the absolute mass of the internal organs of rats showed their direct dependence on body weight and the correlation of these parameters between animals of both groups. The study found that the quantitative ratios of the main hematological parameters of each of the rodents are strictly different. The tendency to increase of the investigated parameters in the experimental group in comparison with the control one is symptomatic and can be explained by sympathetic-vegetative influences. The amount of hemoglobin is directly correlated with the number of red blood cells. Comparison of the content of hemoglobin, erythrocytes, leukocytes with body weight showed inversely proportional relationship between them. The persistent predominance of leukocytes in the blood of rats in both groups is likely to genetically determined.